Chemical Investigations Relating to the Field of Platinum Anticancer Drug Research - Brown, Elaine Brenda (My University, 1988)
Research relating to platinum anticancer drugs follows two schools of thought. One school strives to unravel the mystery surrounding the mechanism of action of these drugs and the second concentrates on developing new platinum drugs superior to those currently available. The work to be discussed relates to both approaches.
The chemistry and structural features of model diammine-dinucleobaseplatinum(II) complexes will be examined and predictions made as to the effects such lesions may have on DNA. In addition, the synthesis and chemicaI characterizations of new pIatinum complexes will be discussed and when possibIe predictions made as to their potential as anticancer agents. The importance of complete and reliable chemical characterizations of these species and others relating to this field will be emphasized.
Keywords: Chemistry; Chemistry